Genetic Variability and Path Coefficient Analysis in Advanced Bread Wheat Lines Using Alpha Lattice Design - Haseeba; Abdur Rauf; Afridi, Khilwat; Yaseen; Elahi, Rahmat; Shakir, Hamadia; Bano, Tayyaba; Nawaz, Laila; Bibi, Haleema; Naz, Amna; Zarghoona; Tariq, Khansa; et al. (Indus Journal of Bioscience Research, 2024)
In 2022-2024 at the Cereal Crops Research Institute, Nowshera, this study was carried out. Sixty-four different genotypes of wheat were evaluated. An experiment based on two replications of alpha lattice design was conducted for various phonological and morphological characteristics. Out of the morpho physiologic features, the highest grain yield was recorded in MPG09 at 5784 kg ha-1, followed by MPG39 at 5777 kg ha-1 and MPG24 at 5496 kg ha-1. The highest biological yield was recorded in MPG40 at 15031.36 kg ha-1. All these features of spring wheat show high positive correlations with each other, as demonstrated by results of this study. Moreover, days to maturity were closely related to plant height, with rg = 0.30, P = 0.05, and flag leaf area, with rg = 0.31, P = 0.05. Plant height showed very strong correlations with flag leaf area, spikelets spike-1, and thousand-grain weight with values of rp = 0.33, P = 0.01; rp = 0.35, P = 0.01; and rp = 0.31, P = 0.05, respectively. Similar positive genetic correlations were recorded for peduncle length with rg = 0.40, P = 0.01, for spikelets spike-1 with rg = 0.75, P = 0.01, and for thousand-grain weight with rg = 0.69, P = 0.01. These findings show that the traits of maturity, plant height and most of the yield variables are interdependent and very important for any crop improvement program. As a statistical method, the path coefficient analysis is used. The variables of 1000-grain weight, tillers per square meter, and peduncle length revealed individual as well as combined effects on grain yield. However, plant height, biological yield, and flag leaf area showed decent indirect effect on grain production. Besides, days to maturity and 1000-grain weight variables had positive indirect effects on the time taken till heading. Similarly, indirect pathways through days to maturity were positive for grain yield: 1000-grain weight added 0.30, tillers per square meter added 0.10, and days to heading added 0.08. The indirect effects of some other traits, such as the peduncle length, spikelets per spike, and flag leaf size, also exerted an effect on grain production. Thus, wheat genotypes MPG09 and MPG39 with higher production can be considered for use in future breeding programs to increase wheat productivity